The new encyclopedia británica in 30 volumen, macromedia Volumen 5 / William Benton - Benton, William (1977)
Diversity, distribution and abundance, economic importance, life cycle, seed development, ecology, the root, leaves, growth and biological production, chemical composition, fossils of contemporary conifers, distinguish taxonomic features, annotated classification, critical appraisal, the history of Connecticut, the natural and human landscape.